Do Female Directors Improve Firm Performance in Sri Lanka? - Pratheepkanth, P. (Uva Wellassa University, 2018)
Boards of Directors play a dominant governance role in organisations and (among other things) seek to ensure that the managerial goals align with those of shareholders and that ineffective management and/or processes do not proliferate. A 100-firms sample, randomly drawn from Colombo stock exchange, was analysed. The results reveal that female board members in Sri Lankan firms averaged 14 percent and ranged from 0-38 percent. Findings also demonstrate that the two performance ratios indicate that each three percent to the observed variability in firm performance is explainable by the female board representation. The significance levels show that both performance models generate statistically insignificant outcomes. Undoubtedly, there is still a gender imbalance in the higher level governance positions Sri Lanka. Female board representation may be a confounding factor that entangles and prevents the influence of board and company attributes from becoming apparent.
Keywords: Board of directors; Female directors; Firm performance